Peningkatan Kompetensi Professional Guru di Era Digital Melalui Pengembangan Pelatihan Berbasis Artificial Intelligence dan Blended Learning - Erwin Novriyanto; Prihastuti Harsani; Soewarto Hardhienata (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims to develop a training model based on Artificial Intelligence (AI) and blended learning to improve the professional competence of elementary school (SD) teachers in the digital era. This research uses the Research and Development (R&D) method with the Borg & Gall approach which involves ten systematic stages. The results of the study show that AI-based training models and blended learning are able to provide adaptive, personalized, and based on the real needs of teachers in the field. The evaluation of the effectiveness of this training model shows an increase in teachers' professional competence in integrating technology in learning. This research makes an important contribution to the development of technology-based teacher training policies in Indonesia.